PENGARUH PEMISAHAN HAK ALIRAN KAS, HAK KONTROL, DAN RETURN ON ASSETS TERHADAP DIVIDEN - Alfiyah Alfiyah; Nur Diana Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2017)
This research entitled "The effect of Cash Flow Separation Right, Right of Control, and Return On Assets To Dividend" The purpose of this research are to know the effect of expropriation of cash flow right, right of control, and return on assets to dividend at manufacturing company listed in Bursa Efek Indonesia during the period 2013-2015.This type of research is quantitative research. The population in this research are 143 manufacturing companies listed on the BEI during the period 2013-2015. Sampling technique used is purposive sampling method. The number of samples obtained 19 companies from 143 manufacturing companies listed on the BEI. The analysis used is multiple linear regression analysis to know the effect of expropriation of cash flow right, right of control, and return on assets to dividend.The results of this research indicate that simultaneously variable separation of cash flow rights, control rights, and return on assets have a significant effect on dividends. Partially, the result of the research shows that the variable of separation of cash flow right has significant positive effect to dividend, while the variable return on assets has no effect on dividend.